Humanizing gears : tensions & harmony - Nur Najiha Puteri Mazian (Nanyang Technological University, 2021)
My project is about gears that behave. Gears as predictable and mechanical as they are, are humanized through adding personal attributes or characteristics that makes us human. These are analog installations where no electronic components are present, but they are meant to "humanize" what we normally perceive as automated. This artwork showcasing two installations - one is a wall installation with suspended balls containing magnets that create shapely figures when it is rotated. The second is a table installation showing crank and sliders that can generate movement of gears containing magnets, creating some form of drawings made on sand.